Correlates of Homeless Episodes among Indigenous People - Whitbeck, Les B. (2012)
This study reports the correlates of homeless episodes among 873 Indigenous adults who are part of an ongoing longitudinal study on four reservations in the Northern Midwest and four Canadian First Nation reserves. Descriptive analyses depict differences between those who have and have not experienced an episode of homelessness in their lifetimes. Multivariate analyses assess factors associated with a history of homeless episodes at the time of their first interview. Results show that individuals with a history of homeless episodes had significantly more individual and family health, mental health, and substance abuse problems. Periods of homelessness also were associated with financial problems. Among the female caretakers who experienced episodes of homelessness over the course of the study, the majority had been homeless at least once prior to the start of the study and approximately one–fifth met criteria for lifetime alcohol dependence, drug abuse, or major depression. Family adversity during childhood was also common for women experiencing homelessness during the study.